Climate change governance for urban resilience for Indonesia: A systematic literature review - Abdillah Abdillah; Rd Ahmad Buchari; Ida Widianingsih; Heru Nurasa (Cogent Social Sciences, 2023)
Cities are faced with new and complex issues such as natural disasters, rapid population growth, and pollution. The era of smart and resilient cities in this century has brought a new type of governance that can explain the ambiguity of urban resilience and the necessary governance of climate change. This research focuses on the discussion of ideal and adaptive climate change governance for urban resilience in Indonesia. This study identifies, reviews, and determines each of the different discussions and literature regarding the extent to which the transition includes aspects of ideal and adaptive governance in Indonesia. To evaluate how urbanization considers the concept of ideal and adaptive governance, this research will also explore trends in adaptive governance that are developing in the world for urban resilience and explain the extent to which climate change governance for urban resilience has been carried out in Indonesia. This research provides guidance to the Indonesian government regarding implementation strategies for dealing with disaster risks due to climate change and offers insights into adaptive climate change governance for urban resilience.